Peran Indivindu dalam Dunia Internasional Studi Kasus: Upaya Nadia Murad, Sang Wanita Peraih Nobel Perdamaian Melawan Ketiranian ISIS - Venisa Yunita Sari (Jurnal Sentris, 2019)
Nadia Murad Basee Taha is a Human Rights Activist, winner of the Nobel Peace Prize in 2018. Nadia Murad was one of the victims of ISIS-related atrocities in 2014. She is one of 6,500 Yazidi women who can be arbitrarily questioned by ISIS militia. Therefore, after being freed from ISIS incarceration, Nadia Murad have been vigorously campaigning to fight for both children and adults’ rights, who were still shackled in the grip of ISIS. This study uses the theory of feminism which then supported by policies, values, norms, and public opinion that have an impact on international realm. This research then formulates answers to research questions relating to the role of individuals in the international world. Through qualitative with descriptive methods, the data sources in this paper come from literature studies by studying books, journals, and research reports. The results of this paper are divided into two important points in explaining the efforts of Nadia Murad in fighting for minority rights in Iraq to be free from the shackles of ISIS. First, Nadia Murad's background. Second, the role of Nadia Murad to fight for and save ISIS prisoners.